Female education and upbringing of women in Medieval Europe: thoughts of contemporaries - Drach, O. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. Medieval culture is an important stage in formation of concepts of female essence by Western civilization. Thinkers introduced a reasoned concept of female imperfections, while the culture of the Middle Ages contained seeds of a new attitude towards women. Purpose. In recent decades there was a tendency of increased interest in female issues in the national historical science. However, many problems in the history of female education and upbringing still remain without attention of researchers. Goal of the article is to study preliminary works of Western European medieval Christian thought on female education and approaches to its implementation. Results. Analysis of didactic works of thinkers of the Middle Ages allows distinguishing three different approaches towards female education. Supporters of the first one have a negative attitude towards the very idea of female education. Among them there were authors of pedagogical works that dealt with boys’ education. Philippe Navarre in his treatise «Four Ages of Man» insisted that a girl should not be taught to read and write. The second approach allowed elementary education for girls (being mostly representatives of the aristocracy). Materials are taken from pedagogical works of the 13th century. Vincent of Beauvais introduced a coherent children’s education system, in which he paid some attention to girls’ education. Giles of Rome recommends all citizens to care about education of daughters to avoid their idle living and to encourage them having permitted and honest occupation. The third approach towards female education provided more advanced education program for girls. Thoughts were described in the treatise French lawyer Pierre Dubois «The Recovery of the Holy Land», who considered it necessary to reform the education system, including through more intensive involvement of women into the education. Conclusion. In terms of womanhood thinkers were unanimous in the matter of formation of a perfect image of female Christian. That image defined standards of girl’s behaviour and character for centuries. Virtuous, innocent, shy, modest, obedient, and gentle – the girl had to be brought up that way. However, education as a component of the female image induced a variety of approaches among authoritative male audience. Most authors considered it reasonable to teach daughters and young wives to read for practical purposes – for their «moral improvement and religious education».